2020
DOI: 10.1002/pros.24078
|View full text |Cite
|
Sign up to set email alerts
|

Association between PSA density and pathologically significant prostate cancer: The impact of prostate volume

Abstract: Background: The early diagnosis of prostate cancer (PCa) is mainly based on prostate-specific antigen (PSA) blood levels and digital rectal examination. However, this approach may result in a high rate of negative biopsies and increased detection of clinically insignificant PCa (CS-PCa). An important prognostic biomarker, PSA density (PSA-D) demonstrated improved performance in PCa detection compared to PSA. The relationship between prostate volume and the prognostic accuracy of PSA-D remains mostly unclear. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 21 publications
4
45
1
1
Order By: Relevance
“…Therefore, many clinical researchers and investigators have recommended that clinicians should counsel patients with large prostates and elevated PSA to consider conservative management such as sequential PSA measurements and not to proceed with biopsies. 22,23 As outlined in this systemic review, many recent, statistically significant and powerful studies are confirming that BPH may be protective against prostatic cancer supporting the proposed mathematical model by Lorenzo et al that growth of the TZ due to BPH causes increased hydrostatic pressure and compresses the PZ (where 80-85% of PCa originates). As mentioned earlier, this histoanatomical process leads to fibrosis and glandular atrophy of the PZ, and thus likely lowers the risk of clinically significant PCa.…”
supporting
confidence: 78%
“…Therefore, many clinical researchers and investigators have recommended that clinicians should counsel patients with large prostates and elevated PSA to consider conservative management such as sequential PSA measurements and not to proceed with biopsies. 22,23 As outlined in this systemic review, many recent, statistically significant and powerful studies are confirming that BPH may be protective against prostatic cancer supporting the proposed mathematical model by Lorenzo et al that growth of the TZ due to BPH causes increased hydrostatic pressure and compresses the PZ (where 80-85% of PCa originates). As mentioned earlier, this histoanatomical process leads to fibrosis and glandular atrophy of the PZ, and thus likely lowers the risk of clinically significant PCa.…”
supporting
confidence: 78%
“…Recent studies have shown that PSAD is associated with CSPCa. In Omri et al's study found that PSAD is correlated with CSPCa (based on radical prostatectomy pathology reports) in small (< 50 cc) and medium (50-75cc) size prostates and level of PSAD is directly associated with the ISUP grade groups (13). In Liu et al's study, univariate and multivariate logistic regression analyses demonstrated that PSAD predicted CSPCa (based on prostate biopsy pathology reports) in the PSA level of 4-10 ng/ml (9).…”
Section: Discussionmentioning
confidence: 98%
“…According to Omri et al, PSA density is associated with csPCa in radical prostatectomy specimens in small- and medium-sized prostate [ 29 ]. In our study, most patients had a small prostate size (<50 mL), PSA density was significantly associated with the PI-RADS score, and there were significant differences in G/S between the three PI-RADS groups.…”
Section: Discussionmentioning
confidence: 99%